Pelibatan dan Pemberdayaan Karyawan (PKK) dalam Total Quality Management (TQM) Pendidikan - Muhamad Fikri Halwan Fauzi; M. Misbah (Pascasarjana Universitas Qomaruddin, 2025)
This study aims to determine how employee involvement and empowerment (PKK) in total quality management (TQM) of education. The method used in this study is a literature review or library study by relying on data sources from various national and international journals indexed in Google Scholar, Garuda, DOAJ, Sinta, Scopus and others to obtain research data. The data analysis technique applied is content analysis, where the literature is read repeatedly and compared to each other to ensure the accuracy of the research results and reduce the possibility of errors. The results of the study indicate that employee involvement includes involvement in various activities and decision making and problem solving. While employee empowerment is to provide meaning and real impact in the involvement. The inhibiting factors for employee involvement and empowerment (PKK) in total quality management (TQM) are the lack of top management commitment, wrong focus of attention, gaps in top management commitment, employee work culture and excessive worry factors.